Pengaruh Konsentrasi Surfaktan dan Permeabilitas pada Batuan Sandstone terhadap Perolehan Minyak dalam Proses Imbibisi (Laboratorium Study) - Tri Yoga Prasojo; Sugiatmo Kasmungin (Journal of Mechanical Engineering and Mechatronics, 2017)
There are three levels in producing oil or natural gas: primary recovery where oil flows into the wellbore by itself; secondary recovery where oil flows with the help of water or gas injection; and tertiary recovery, commonly called Enhance Oil Recovery (EOR). Total recovery from one oil field is about 50% -60% of OOIP. With primary and secondary recovery 30% -40% can be obtained from OOIP, it is expected that the remaining 20% -30% can be taken with EOR. This study investigated EOR by injection of various surfactant concentrations at temperatures of 30°C and 80°C using brine with salinity of 10,000 ppm by imbibition. The aim of this research is to know the effect of surfactant concentration and salinity of the formation water on oil acquisition in relation to sandstone permeability, and to find out what level of concentration to the average permeability rate with temperature close to reservoir average temperature (80°C), can be obtained a minimal Sor so that RF (Recovery Factor) to be maximal. The methodology used is to measure: the physical properties of rocks and fluids (the solution used), the interface voltage and selected the best solution (the smallest interface voltage), and soaking the rock with Amot test glass. From this study, it can be concluded that the addition of concentration will decrease the density, but the addition of temperature will decrease the density and viscosity; the addition of the surfactant and temperature concentration will decrease the interface voltage until the CMC point is reached; good permeability and porosity may not produce good results when clay contamination is present